A fiber-modified adenovirus co-expressing HSV-TK and Coli.NTR enhances antitumor activities in breast cancer cells - Zhan, Yang (e-Century Publishing Corporation, 2014)
Breast cancers especially in late and metastatic stages remain refractory to treatment despite advances in surgical techniques and chemotherapy. Suicide gene therapy based on adenoviral technology will be promising strategies for such advanced diseases. We previously showed that co-expression of herpes simplex virus thymidine kinase (HSV-TK) and Escherichia coli nitroreductase (Coli.NTR) by an hTERT-driven adenovirus vector resulted in additive anti-tumor effects in breast cancer cells in vitro and in vivo. As many tumor tissue and cancer cells express low level of coxsackie-adenovirus receptor (CAR), which is the functional receptor for the fiber protein of human adenovirus serotype 5 (Ad5), novel Ad5 vectors containing genetically modifi ed fiber are attractive vehicles for achieving targeted gene transfer and improving suicide gene expression in these cancer cells. In the present study, we first built a simplified Ad5 vector platform for fiber modification and quick detection for gene transfer. Then a fiber-modified adenovirus vector containing an RGD motif in the HI loop of the fiber knob was constructed. After recombined with HSV-TK and Coli.NTR gene, this fiber-modified Ad5 vector (Ad-RGD-hT-TK/NTR) was compared with that of our previously constructed Ad5 vector (Ad-hT-TK/NTR) for its therapeutic effects in human breast cancer cell lines. The anti-tumor activity of Ad-RGD-hT-TK/NTR was significantly enhanced compared with Ad-hT-TK/NTR both in vitro and in vivo. This new vector platform provided a robust and simplified approach for capsid modification, and the fiber-modified Ad5 with double suicide genes under the control of hTERT promoter would be a useful gene therapy strategy for breast cancer.